Effects of high-intensity interval training on pulmonary function - Dunham, C.; Harms, C. A. (European Journal of Applied Physiology, 2012)
To determine whether high-intensity interval training (HIT) would increase respiratory muscle strength and expiratory flow rates more than endurance training (ET), 15 physically active, healthy subjects (untrained) were randomly assigned to an ET group (n = 7) or a HIT group (n = 8). All subjects performed an incremental test to exhaustion (VO2max) on a cycle ergometer before and after training. Standard pulmonary function tests, maximum inspiratory pressure (PImax), maximum expiratory pressure (PEmax), and maximal flow volume loops were performed pre training and after each week of training. HIT subjects performed a 4-week training program, 3 days a week, on a cycle ergometer at 90% of their VO2max final workload, while the ET subjects performed exercise at 60-70% VO2max. The HIT group performed five 1-min bouts with 3-min recovery periods and the ET group cycled for 45 min continuously. A five-mile time trial (TT) was performed prior to, after 2 weeks, and after completion of training. Both groups showed improvements (P < 0.05) in VO2max (~8-10%) and TT (HIT 6.5 ± 1.3%, ET 4.4 ± 1.8%) following training with no difference (P > 0.05) between groups. Both groups increased (P < 0.05) PImax post training (ET ~ 25%, HIT ~ 43%) with values significantly higher for HIT than ET. There was no change (P > 0.05) in expiratory flow rates with training in either group. These data suggest that both whole-body exercise training and HIT are effective in increasing inspiratory muscle strength with HIT offering a time-efficient alternative to ET in improving aerobic capacity and performance.